Oral nitrate reduction is not impaired after training in chlorinated swimming pool water in elite swimmers - Rowland, S. N.; Chessor, R.; French, R.; Robinson, G. P.; O`Donnell, E.; James, L. J.; Bailey, S. J. (Applied Physiology, Nutrition, and Metabolism, 2021)
This study tested the hypothesis that exposure to chlorine-sterilised pool water would impair oral nitrate reduction (ONR). ONR was assessed in elite swimmers before and after morning and afternoon pool-based training. Nonswimmers were only assessed in the morning. ONR was similar in swimmers and nonswimmers (P = 1.000) and unchanged before and after morning and afternoon training (P = 0.341). Therefore, exposure to chlorinated pool water does not interfere with ONR. Novelty Exposure to chlorine-sterilised pool water does not impair oral nitrate reduction in elite swimmers.